Problem Based Learning (PBL) in Competence Based Curriculum and The Accademic Achievement: Evaluation of PBL Implementation - Kusumawati, Wiwik (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2012)
Background: Medical Faculties in Indonesia has implemented problem based learning (PBL) in competence based curriculum as a learning strategy. The aim of this study is to know the effect of PBL method on academic achievement and factors affecting successfull PBL implementation.Design and Method: This study used quantitative and qualitative method. Data collection method is by distributing questionnaires, focus group discussion (FGD) and document analysis of students’ academic achievement. This study included 3 year level students (2004, 2005, 2006) using PBL in school of medicine faculty of medicine and health sciences UMY (FMHS UMY).Result: GPA average > 2.5 is 32.47 %, MCQ > 60 is 33.1% and OSCE is 92.8%. The role of tutor and also practical instructor to facilitate learning objective was not optimal. The factors for the poor implementation of PBL includes curriculum planning (understanding of PBL concept and dissemination of curriculum), implementation of curriculum (various of block load, opportunity for self directed learning, e-learning effectivity, etc) and assessment system (the number of students who reach minimal standar of MCQ is low, validity of MCQ is also low, etc).Conclusion: This study suggest the need to improve planning, implementation and curriculum assessment to support implementation of PBL. The role of Lecturer, tutor and practical instructor should be improved through faculty development to faciliate teaching learning proccess in PBL method (Sains Medika, 4(1):30-38).